Concealed Information Test with Combination of ERP Recording and Autonomic Measurements - Farahani, E.D.; Moradi, M.H.A. (Нейрофизиология, 2013)
The concealed information test (CIT) is based on a comparison between the subject’s physiological responses to a probe and irrelevant items in order to detect concealed information. The main purpose of our study was to investigate the CIT accuracy enhancement related to a combination of recording of event-related potentials (ERPs) and autonomic measurements. We tried to maximally liken the experimental conditions to real ones by the use of a criminal context in the “mock crime” instruction and real innocent subjects instead of hypothetical ones. Fifty-two subjects volunteered and performed just one of the innocent or guilty scenarios. The CIT was designed in five blocks with short interstimulus intervals. In each block, stimuli were presented in the 7th-order balanced sequence. In addition to EEG phenomena, the heart rate, skin conductance responses (SCRs), respiratory activity, and finger plethysmogram were recorded. Statistical analyses showed that there was a significant difference between standardized difference scores of the guilty and innocent groups in both ERP and autonomic measures. The SCR did not achieve the expected results reported in standard autonomic-based CIT studies. A review of the two classification methods showed that the combination of ERP and autonomic measurements enhances the CIT accuracy. The best classification accuracy obtained by the aid of linear discriminant analysis (LDA) was 90.9%. It seems that using a criminal context in the “mock crime” instruction and the rewardpunishment system made subjects more attentive and involved in the experiment; therefore, the accuracy was improved compared with that in similar studies Тест із прихованою інформацією (ТПІ) базується на порівнянні фізіологічних реакцій суб’єкта в зондуючих і нейтральних ситуаціях, спрямованому на виявлення такої інформації. У нашій роботі ми визначали точність результатів ТПІ в умовах, коли цей тест поєднували з відведенням пов’язаних з подією потенціалів (ППП) і вимірюванням вегетативних показників. Особливістю нашого дослідження було максимальне наближення експериментальних умов до реальних за допомогою використання кримінального контексту в інструкції „макетування злочину” та „реально невинуватих” суб’єктів замість „гіпотетично невинуватих”. 52 волонтери виконували один із сценаріїв „винуватий/невинуватий”. ТПІ вміщував п’ять блоків з короткими міжстимульними інтервалами. У кожному з блоків стимули пред’являлись у балансованій послідовності сьомого порядку. Крім ЕЕГ-активності, реєстрували частоту пульсу, зміни шкірної провідності (ШП), дихальну активність і плетизмограму пальців. Статистичний аналіз показав, що між стандартизованими оцінками відмінностей характеристик як ППП, так і вегетативних показників у „винуватій” та „невинуватій” групах виявлялися вірогідні відмінності. При виявленні змін ШП очікувані результати, описані для стандартних результатів ТПІ, що базуються на вимірювання вегетативних показників, не досягалися. Порівняння двох класифікаційних методик показало, що поєднання відведення ППП і вегетативних вимірювань підвищує точність результатів ТПІ. Найбільша точність класифікації, отриманої із застосуванням лінійного дискримінантного аналізу, складала 90.9 %. Скоріш за все, використання кримінального контексту в інструкції „макетування злочину” і системи преміювання/покарання забезпечувало більший рівень уваги тестованих та їх більше залучення в експеримент, що й підвищувало точність тестування порівняно з такою в аналогічних дослідженнях